Optimalisasi Manajemen Administrasi Kependidikan Melalui Digitalisasi Sistem Pendaftaran Peserta Didik Baru: Studi Dampak Efisiensi Operasional - Lentera Bawono (Jurnal Ekonomi dan Teknik Informatika (JNETI), 2026)
In the era of digital transformation, operational efficiency in educational administration has become a crucial parameter for institutional sustainability. However, many madrasahs in sub-urban areas still face challenges of inefficiency due to manual registration systems prone to data errors and time consumption. This study aims to analyze the optimization of educational administrative management through the implementation of a web-based New Student Admission System (PPDB) at MTs Ma’Arif NU Kemiri Winong and evaluate its impact on operational efficiency. This research employs a descriptive case study approach with in-depth observation and interview methods to compare efficiency parameters before and after digitalization. The evaluation matrix focuses on data processing time, information accuracy, and administrative cost savings. The research findings indicate that the digitalization of PPDB successfully reduced registration processing time by 80%, eliminated data redundancy through real-time validation, and significantly lowered administrative operational costs. Furthermore, the system enhanced data transparency and the professional image of the institution in the public's perception. This study concludes that digitalization is not merely a technical solution but a strategic catalyst in transforming madrasah management to achieve accountable and efficient governance.